Dampak Dari Kekuatan Dan Popularitas Selebgram Terhadap Minat Beli Pada Produk Mode Lokal Di Instagram - Irpansyah, Muhamad Alvi; Ramdan, Asep M.; Danial, R. Deni Muhammad (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.03.TAHUN 2019, 2019)
The study aims to determine about the effect of selebgram power and visibility to purchase intention on local fashion product in instagram, as well as to see how much the influence of selebgram power and visibility to purchase intention partially or simultaneously. The method use in this research is descriptive verificative and quantitative approaches with multiple linear regression as a data analysis technique. Research result obtained show that power, visibility and purchase intentions in the good category. The magnitude of the effect of selebgram power and visibility on purchases intention on instagram by Rachel Vennya after testing simultaneously and partially have a positif and significant influence. It’s amounted to 48,2%, while the remaining 51,8% are influenced by other variables not examined in this research.